2011
DOI: 10.1007/s10571-011-9653-x
|View full text |Cite
|
Sign up to set email alerts
|

Latanoprost Promotes Neurite Outgrowth in Differentiated RGC-5 Cells via the PI3K-Akt-mTOR Signaling Pathway

Abstract: Latanoprost, a synthetic derivative of the natural prostaglandin F(2a) (PGF(2a)), is a powerful antiglaucoma agent with ocular hypotensive and neuroprotective effects. However, the neuroregenerative effect and signaling pathway of latanoprost in retinal ganglion cells (RGCs) are still unknown. The purpose of this study is to investigate the regenerative effect of latanoprost in differentiated RGC-5 cells and its underlying mechanisms. Cell viability was determined by Cell Counting Kit-8 (CCK-8) assay and neuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 36 publications
0
19
0
2
Order By: Relevance
“…19, 21, 22, 23, 40, 41, 42, 43, 44, 45, 46, 47 We examined the effects of specific inhibitors for these molecules on neurite outgrowth. The PLC-γ inhibitor, U73122 (1.0 μℳ), PI3K inhibitor, LY294002 (10 μℳ), mTOR inhibitor (rapamycin; 5.0 μℳ), p38 MAPK inhibitor, SB203580 (10.0 μℳ), JNK inhibitor, SP600125 (10 μℳ) and Akt inhibitor (1.0 μℳ) significantly blocked aripiprazole's potentiation of NGF-induced neurite outgrowth (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…19, 21, 22, 23, 40, 41, 42, 43, 44, 45, 46, 47 We examined the effects of specific inhibitors for these molecules on neurite outgrowth. The PLC-γ inhibitor, U73122 (1.0 μℳ), PI3K inhibitor, LY294002 (10 μℳ), mTOR inhibitor (rapamycin; 5.0 μℳ), p38 MAPK inhibitor, SB203580 (10.0 μℳ), JNK inhibitor, SP600125 (10 μℳ) and Akt inhibitor (1.0 μℳ) significantly blocked aripiprazole's potentiation of NGF-induced neurite outgrowth (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Nakazawa et al created an ischemic model of optic nerve injury with optic nerve crush and found that PI3K/Akt pathway activation produces a neuroprotective effect against retinal and optic nerve injury [39]. Moreover, the P13K/Akt signaling pathway can contribute to the neurite outgrowth of differentiated RGCs [40]. Therefore, this pathway is needed to inhibit the occurrence of apoptosis and promote axonal regeneration in both glaucoma and optic neuropathy [41, 42].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this same study found that COX-2 activity was reduced by both arachidonic acid and latanoprost in RGCs exposed to excess glutamate and that inhibition of inducible nitric oxide synthase occurred with the same drug concentrations. Latanoprost may also exhibit a direct anti-apoptotic effect via neurite outgrowth and caspase-3 inhibition, mediated by p44/p42 mitogen-activated protein kinase [98,99]. There are several other hypotheses regarding secondary neuroprotective mechanisms for prostaglandin analogs, including effects on ocular and ONH hemodynamics [100,101].…”
Section: Prostaglandin Analogsmentioning
confidence: 99%